A responsive pedagogical initiative for multimodal oral presentation skills: an action research study - Lee, Sze Seau; Hazita Azman,; Noorizah Mohd. Noor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Poor oral presentation skills amongst ESL speakers are frequently linked to weakness in general English proficiency. However, the literature has also identified the lack of a systematic and effective pedagogical method to develop students' multimodal oral presentation skills to meet 21st century communication realities. This paper elucidates the application of a pedagogical initiative for multimodal oral presentations skills, informed by the Sociocultural Theory of Learning created by Vygotsky (1978), and the Pedagogy of Multiliteracies introduced by the New London Group (1996) and further developed by Cope and Kalantzis (2009). This initiative was experienced by 20 students through the action-reflection cycle methodology and was implemented for 13 weeks in a tertiary ESL classroom. Preliminary findings based on focus group interviews indicated that the initiative left a clear positive impact on student abilities in various multimodal components of oral presentation skills. Furthermore, the initiative positively affected students’ learning experience and raised their self-awareness of themselves as presenters. The findings also suggested that techniques employed in the initiative such as videos, feedback, collaborative learning and Web 2.0 could scaffold the students’ development of multimodal oral presentation skills. Based on these findings, significant implications for teaching oral presentation skills systematically are offered to be referred by ESL practitioners and researchers; in particular, the proposed multimodal oral presentations skills model as a multiliteracies pedagogy and the potential use of web 2.0 tools in promoting collaborative learning and creation of creative content by the learners.